Peraturan Pemeliharaan Anak dalam Hukum Adat Bali Akibat Perceraian Putusan No.36/Pdt.G/2016/Pn.Ng - Lisa Aprilia Gusreyna; Siti Kotijah (Jurnal Risalah Hukum, 2022)
In Hinduism, divorce is highly avoided, because it is an act of Adharma or sin. The approach used is a doctrinal approach with the aim of knowing two main points of discussion: First, the author wants to develop child care in Balinese customary law due to divorce. Second, the writer wants to analyze the decision No.36/PDT.G/2016/PN.Ng. Based on the results of the study, it can be said that the Balinese patrilinear system is the basis for the struggle for children's rights, as a result of divorce both purusa custom, Hindu religion, and the Supreme Court decision No.36/PDT.G/2016/PN which places a man, namely the father. as a babysitter. Keywords: divorce; balinese customs; child care